(untitled) (Research, Society and Development, 2023)
This study had the general objective of demonstrating whether the municipalities of the State of Tocantins are showing depreciation in their balance sheets and explanatory notes. The population is made up of all city halls in the State of Tocantins, and the sample comprises 39 city halls with the highest average investment in non-current assets in relation to total assets for the years 2017, 2018 and 2019. Data collection was carried out in the website of the State of Tocantins Court of Auditors (TCE-TO) in relation to information on the Balance Sheet, Statement of Equity Changes and Explanatory Notes. Analyzes were performed using the quantitative method. As a result of the study, it can be observed in general terms, as the municipalities of the State of Tocantins did not exactly obey the depreciation rules referring to NBC TSP 07 in the analyzed period. How to demonstrate the city of Guaraí in 2017, showing 0.18% of accumulated depreciation in relation to the value of its fixed assets, as well as the city of Augustinópolis in 2018, which showed only 0.17% of accumulated depreciation on the value of its fixed assets, likewise the city hall of Axixá do Tocantins, which in 2019 showed 0.01% of depreciation in relation to the value of the equity result.